Factores de riesgo en pacientes adultos con cateterismo periférico, ingresados en el Hospital Abel Gilbert Pontón en la ciudad de Guayaquil en el periodo octubre 2019 – marzo 2020 - García Luna, Dinora Del Carmen (2020)
Peripheral catheterization refers to the insertion of the catheter into a peripheral artery, vein or vascular pathway for diagnostic or therapeutic purposes. The World Health Organization indicates that 70% of patients have some type of venous catheter and 38% of peripheral pathways are not necessary, there are several risk factors that influence the development of complications in the area of channeling. The objective will be to identify the risk factors in adult patients with peripheral catheterization, admitted to the Abel Gilbert Pontón Hospital in the city of Guayaquil in the period October 2019- March 2020. The qualitative and quantitative identification methodology, the population was formed For 200 patients hospitalized in the area of surgical specialties, the sampling formula was applied obtaining a sample made up of 53 adult patients with peripheral catheterization admitted to the Abel Gilbert Pontón Hospital and 7 nursing licenses in a charge of the area of surgical specialties . 71% of the nursing staff indicates that the bad practice in the insertion of the peripheral venous catheter will lead to the development of complications such as phlebitis, extravasation and communication that has not socialized protocols or norms of peripheral canalization management. A training schedule on peripheral venous canalization management is proposed for nursing professionals at the "Abel Gilbert Pontón" Hospital.